2023
DOI: 10.1097/ms9.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the emergency department by kidney transplant recipients: a retrospective cohort study from a high-volume transplant center

Belal Nedal Sabbah,
Mohammad Alghafees,
Ahmad Nedal Sabbah
et al.

Abstract: Background: This study aims to assess the trends of emergency department (ED) visits among kidney transplant recipients in a high-volume transplant centre. Methods: This retrospective cohort study targeted patients who underwent renal transplantation at a high-volume transplant centre from 2016 to 2020. The main outcomes of the study were ED visits within 30 days, 31–90 days, 91–180 days, and 181–365 days of transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Out of 5225 visits to the ED, 2265 (41%) were within the first year, and 1,501 (66%) of those visits were within the first six months. Two similar studies had shown similar results, with ED visits within the first six months accounting for 60% of total visits within the first year [ 14 , 16 ]. The study conducted in South Korea was more similar to this study’s methodology, with visits three years post-live transplant being assessed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Out of 5225 visits to the ED, 2265 (41%) were within the first year, and 1,501 (66%) of those visits were within the first six months. Two similar studies had shown similar results, with ED visits within the first six months accounting for 60% of total visits within the first year [ 14 , 16 ]. The study conducted in South Korea was more similar to this study’s methodology, with visits three years post-live transplant being assessed.…”
Section: Discussionmentioning
confidence: 64%
“…Our study aims to characterize liver transplant patients’ visits to the ED and identify any risk factors that contributed to those visits. Along with the very recent study assessing kidney transplant patients’ visits to the ED [ 14 ], this study will provide a better understanding and picture of the current status of organ transplant patients’ visits to the ED.…”
Section: Introductionmentioning
confidence: 99%